Performance Patrol Unit Turjawali Sat Same Police Office Malang in Prevention of the Criminal Act of Theft with Violence - ilham, bagasrafi; Iswanto, Ganang; Mandica, Andi Gibran Gani (Tanggon Kosala, 2024)
Malang Regency is one of the largest regencies in East Java Province; besides that, Malang Regency also occupies the second position in the population density in East Java Province after Surabaya City. The dense population in Malang Regency resulted in high unemployment rates in Malang Regency. Most residents of Malang Regency who do not have a profession choose shortcuts to meet their daily needs by committing theft. One type is violent theft. This research uses a type of qualitative research according to a qualitative approach according to Hardani and his team in his book Qualitative and Quantitative Research Methods (Hardani et al, 2020: 39) is scientific research by describing the collection and process of qualitative data, namely data taken descriptively from the social symptoms studied which will be checked from one source to another to answer questions until the results of the information are considered sufficient, complex and correct so that they can be used as research results. The performance of the Samapta Unit in preventing motor vehicle theft in the jurisdiction of the Malang Regional Police is still inefficient and ineffective. Note that it is inefficient due to a lack of organizational input and inability to produce a high output, so low productivity, and individual performance are still lacking. While it has not been effective, because, from the objective approach, it is proven by the inequality between the implementation of patrols and the guidelines made; besides that, the number of criminal acts of violent theft has not been prevented, and the number has increased. Then, from the internal process approach, in the Samapta unit, there are still obstacles in personnel backups that still lack coordination.